Analisis Faktor Minat dan Faktor Kemampuan Yang Mempengaruhi Mahasiswa Memilih Jurusan Pendidikan Matematika - Rama Nida Siregar (Lembaga Bale Literasi, 2024)
The purpose of this study was to explain the interest factors and ability factors that influence students to choose the TMM education and teaching major at UIN SYAHADA Padangsidimpuan, totaling 150 students. This study uses a qualitative descriptive approach. The method of data source sampling is purposive and snowball, the method of triangulation data collection (combined), inductive/qualitative data analysis, and the results of qualitative research emphasize the method on a common basis. The results of the study showed that there were factors that influenced students in choosing the education/teaching major in mathematics at the Faculty of Teacher Training and Education, UIN SYAHADA Padangsidimpuan. After analyzing the information that the researcher collected, it was found based on the results of the analysis of the questionnaires distributed and interviews with respondents/students who were active in the TMM department, several effective factors in the field were found that influenced students to choose the TMM section, namely internal/self factors including interest and ability factors. Based on these results, it shows that the factors that influence students to choose the TMM department at UIN SYAHADA Padangsidimpuan include interest factors and ability factors. The interest factor is related to the choice of TMM students' majors at UIN SYAHADA Padangsidimpuan, namely the students' interest in the TMM major they choose. Of all the problems answered by TMM students, there were 59 respondents who were in accordance with their interests in choosing the TMM major. Furthermore, the ability factor is one of the factors that influences students in choosing the TMM major at UIN SYAHADA Padangsidimpuan, namely with the ability of students will provide better results when choosing the TMM major. From the total statements answered by TMM students, 34 respondents were selected from the ability factor.